Analysis of Student Representation Ability in Solving First Law Problems of Thermodynamics - Dai, Windi Rianti; Nurjannah (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2023)
The research was meant to analyze the student's ability to representation the problem of thermodynamics. Research time was done on the oddity of the school year 2021/2022. This method of study is a mixed study with a type of explanatory sequential mixed items. The subject of this study is the 2020 class of physical education students in the physics education study program, the university of tadulako as many as 15 people. The respondents in this study are the subject of a selected study that represents three strategies of high, moderate, and low as many as three. The problem-solving test instruments use student representation of the essay tests the lab was botched by the validator able The acquisition of the problem-solving skill test using representation shows that the average score for 15 human research subjects is 59.13 and deviation of 6.39. Research shows that students tend to be weak in resolving problems with graphic and mathematical representation. The dominant representation format is dominated by the student's verbal representation ability, the concept of the student in particular on the representation should be enhanced by getting the student to solve the problem with the representation form of verbal, mathematical paragraph on learning.